Features of the treatment of exudative otitis media in children of the Black Sea region (Odessa and Chernomorsk, Ukraine) - Tagunova, I.; Andreev, A.; Drahniev, M.; Padalka, S.; Gushcha, S.; Zukow, W. (Journal of Education, Health and Sport, 2020)
<p class="western" style="margin-bottom: 0cm; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="uk-UA" align="justify">Among non-purulent inflammatory diseases of the ear in children, exudative otitis media is in second place. The purpose of the work is the development of algorithms to increase the effectiveness of treatment of children with exudative otitis media of various age groups. Practical conclusion: therapeutic tactics have their own characteristics; conservative treatment is advisable for two weeks, while maintaining the exudate beyond the specified period, an operation is indicated - shunting of the tympanic cavity.